Status of Bombay duck Harpodon nehereus (Ham.) resource off Saurashtra coast - Khan, Mohammad Zafar; Kurup, K N; Lipton, A P (Indian Journal of Fisheries, 2011)
The Bombay duck Harpodon nehereu.' (Ham.) landings along the Saurashtra coast showed a decliningtrend with an average catch of32 645 tOMeslyear during 1984-89. Basic food consisted of its own young ones,Acetes spp., Nematopalaemon tenuipe,f. The species breed throughout the year with peaks during DecemberJanuaryand June. The size at first maturity was 232.5 mm. Individual fish spawned once a year and fecundityvaried between 17075 and 79 631. Average fecundity was 340 ovalg body weight.The growth parameters L. and K were estimated. The fishing mortality coefficient (F) for the period was1.009 while natural mortality was 1.535. The MSY was estimated as 34 668 at F ... 1.119